Poverty, environment and sustainable development : how the Commonwealth supports implementation of the World Summit on Sustainable Development - Strachan, Janet (2003)
Focuses on environment-related work that could be implemented by the Commonwealth Secretariat in response to the Summit. Reviews recent work linked to specific aspects of the Plan of Implementation across all three pillars of sustainable development.